Bamboo shoots after the rain: Development and challenges of autism intervention in China. (September 2013) - McCabe, Helen
The purpose of this study was to gain an in-depth understanding of autism intervention in China, including history, progress, and current challenges. This qualitative research study included interviews with experienced professionals and observation at autism intervention organizations. Analysis of this empirical data led to three themes regarding this field. First, the development of the field can be described using the Chinese expression, mozhe shitou guohe (feeling stones to cross the river). Owing to limited exposure to outside information, methods are often created independent of research-based best practices. Second, autism intervention in China has had a strong, and until recently, almost exclusive, focus on young children. Finally, there are continued challenges to providing effective services that relate to the desires of parents and professionals to provide 'more'; a focus on quantity may be preventing a focus on quality. The article concludes with an analysis of the findings and practical implications that may be used by practitioners or scholars planning to do work in China.